To determine the angle measures in the given situation, we know that angles \( \angle ABC \), \( \angle ABD \), and \( \angle DBC \) together form a right angle at point B, which measures \( 90^\circ \).
Given:
- \( \angle ABC = 90^\circ \)
- \( \angle ABD = 4x^\circ \)
- \( \angle DBC = (7x - 9)^\circ \)
Since \( A, D, \) and \( C \) form a right angle at B, we can set up the equation based on the sum of angles. The equation will be:
\[ \angle ABD + \angle DBC = \angle ABC \]
Substituting the values we have:
\[ 4x + (7x - 9) = 90 \]
This creates the equation for determining the angle measures. The simplified equation based on your prompt would be:
\[ 4x + (7x - 9) = 90 \]
This can be rearranged as:
\[ 4x + 7x - 9 = 90 \]
So, the concise representation for the equation based on your format is:
\[ (4x)° + (7x - 9)° = 90° \]